2013
DOI: 10.5993/ajhb.37.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Issues in Biomedical Research: What Do Hispanics Think?

Abstract: Objective To examine barriers and facilitators of biomedical research participation among Hispanics in a rural community in Washington State. Methods Questionnaires addressed socio-demographics, health care access, and barriers and facilitators of participation in biomedical studies. This is a descriptive analysis of the findings. Results Barriers include the need to care for family members (82%), fear of having to pay for research treatments (74%), cultural beliefs (65%), lack of time (75%) and trust (71%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 12 publications
2
22
1
Order By: Relevance
“…In contrast to previous studies (Davis, Bynum, Katz, Buchanan, & Green, 2012; Ulrich et al, 2013) a limited number of participants noted a lack of access to participation opportunities, simply “not being asked”, or a lack of trust as additional barriers. Interpretation of these particular findings, however, should be done with caution as some of the perceptions about community members’ level of motivation, interest in health-related information, and level of education may be the result of internalized racism as opposed to accurate portrayal of educational or motivational barriers to participation among Latinos in this community.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In contrast to previous studies (Davis, Bynum, Katz, Buchanan, & Green, 2012; Ulrich et al, 2013) a limited number of participants noted a lack of access to participation opportunities, simply “not being asked”, or a lack of trust as additional barriers. Interpretation of these particular findings, however, should be done with caution as some of the perceptions about community members’ level of motivation, interest in health-related information, and level of education may be the result of internalized racism as opposed to accurate portrayal of educational or motivational barriers to participation among Latinos in this community.…”
Section: Discussioncontrasting
confidence: 90%
“…Additionally, there is evidence that logistical factors such as lack of transportation, limited access to medical resources, and concern about needing to pay for research services can act as barriers to Latinos’ research participation (Ulrich et al, 2013). Cultural factors have been found to contribute to differential recruitment and retention of minority racial and ethnic populations in clinical trials (Eggerth DE & Flynn MA, 2010; Sheppard et al, 2005), but there is limited data on whether cultural factors similarly influence Latinos’ decisions to take part in biomedical research.…”
Section: Introductionmentioning
confidence: 99%
“…(Buchwald et al, 2006) Additionally, several underrepresented groups have demonstrated a fear of participation due to lack of transparency and low comprehension of the informed consent process.(G. Corbie-Smith et al, 1999; Shaw, Robinson, Starks, Burke, & Dillard, 2013; Ulrich et al, 2013)…”
Section: Discussionmentioning
confidence: 99%
“…Other barriers may have included cultural factors, mistrust of researchers, and practical issues such as lack of time, transportation, or childcare. 21,22 We face ongoing challenges in recruitment for the ORT study, which amongst the four studies has the lowest percentage of eligible women participating. One possible reason is perceived study burden: three blood draws and two transvaginal ultrasounds that require timing to the participant's menstrual cycle.…”
Section: Local Recruitment Challenges and Recommendationsmentioning
confidence: 99%